The Influence of Inspectorate General Auditor Quality, Accountability, and Supervision on the Quality of Financial Statements of the Jakarta Provincial Government - Siti Maharani; Adam Zakaria; Muhammad Yusuf (Journal of Business Innovation and Accounting Research, 2024)
This study aims to examine the influence of the Inspector General's auditor quality, accountability, and supervision on the quality of the Jakarta Provincial Government's financial statements. The study population consists of employees of the Inspectorate General of Jakarta Province. A purposive sampling technique was employed, resulting in 45 respondents who met the research criteria. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that the quality of Inspectorate General auditors, accountability, and supervision have a positive and significant effect on the quality of financial statements of the Jakarta Provincial Government. The coefficient of determination (R²) demonstrates that 73.6% of the variance in financial statement quality is explained by these three variables.